Koncepcje i metody strategicznej rachunkowości zarządczej - Nowak, Edward (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article discusses of the strategy-oriented management accounting. It shows the constraints of the traditional management accounting which is targeted towards the operational management. Against this background, the role and importance of a managerial accounting in the strategic management process was depicted. Also the concept of the strategic management accounting was shown as well as the methods of strategic management accounting used in theory and practice. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1178, s. 93-99